Denitrification of nitrate contaminated groundwater with a fiber-based biofilm reactor - Wang, Qinghong; Feng, Chuanping; Zhao, Yingxin; Hao, Chunbo (Bioresource technology, 2009)
A fiber-based biofilm reactor was developed using a laboratory-scale apparatus for treatment of nitrate-contaminated groundwater. Denitrification bacteria were inoculated by anaerobic sludge from a wastewater treatment plant. Nitrate removal efficiency, nitrite accumulation, COD and pH in the treated water were investigated under various conditions set by several parameters including hydraulic retention times (HRTs) (24, 20, 16, 12, 8, 4 and 2 h), influent nitrate loading (around 50, 100 and 150 NO 3 - – N mg L - 1 ), pH (5, 6, 7, 8, and 9) and ratios of carbon to nitrogen (C/N = 3.00, 2.00, 1.50 1.25 and 1.00). The experimental results demonstrated that the optimum reaction parameters were pH 7–7.5,C/N = 1.25 and HRT = 8 h, under which over 99% of NO 3 - – N was removed, almost no NO 2 - – N accumulated and COD was nearly zero in treated water when the concentration of NO 3 - – N was around 100.00 mg L −1 in influent.